2010
DOI: 10.1007/s10597-010-9319-z
|View full text |Cite
|
Sign up to set email alerts
|

Review: Community-Based Participatory Research Approach to Address Mental Health in Minority Populations

Abstract: In this review, a synthesis of studies employing community-based participatory research (CBPR) to address mental health problems of minorities, strengths and challenges of the CBPR approach with minority populations are highlighted. Despite the fact that minority community members voiced a need for innovative approaches to address culturally unique issues, findings revealed that most researchers continued to use the traditional methods in which they were trained. Moreover, researchers continued to view mental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
63
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 22 publications
2
63
0
5
Order By: Relevance
“…This points to the need to pursue alternate avenues in addressing ethnic and racial disparities in mental health, in particular, avenues that allow for the integration of mental health interventions into the everyday life of ethnic minority and immigrant children and families. For example, one promising approach employs community-based participatory methods in which the communities themselves are active, equal partners in designing interventions that are culturally congruent and acceptable (Stacciarini et al 2011). As researchers and practitioners partner with local ethnic and immigrant communities, the CIE can serve as a guiding framework for developing culturally and community-driven approaches to bringing mental health interventions to the doorsteps of ethnic minority and immigrant families.…”
Section: Discussionmentioning
confidence: 99%
“…This points to the need to pursue alternate avenues in addressing ethnic and racial disparities in mental health, in particular, avenues that allow for the integration of mental health interventions into the everyday life of ethnic minority and immigrant children and families. For example, one promising approach employs community-based participatory methods in which the communities themselves are active, equal partners in designing interventions that are culturally congruent and acceptable (Stacciarini et al 2011). As researchers and practitioners partner with local ethnic and immigrant communities, the CIE can serve as a guiding framework for developing culturally and community-driven approaches to bringing mental health interventions to the doorsteps of ethnic minority and immigrant families.…”
Section: Discussionmentioning
confidence: 99%
“…Sería necesario poder ampliar estos resultados con una muestra mayor. Por otra parte, sería interesante poder contrastar estos resultados con la visión que poseen los propios residentes del hogar/residencia; para ello, se podría trabajar bajo un modelo de investigación basada en la participación de la comunidad que promueva durante el proceso los principios del modelo de SMC que se desean potenciar (Stacciarini, Shattell, Coady, & Wiens, 2011).…”
Section: Discussionunclassified
“…Marcus et al (64) explicitly utilized principles of community-based participatory research (CBPR), where members of the target population are engaged in the entire research process from planning, implementation, analysis, and evaluation (77). A recent review concluded that CBPR has "great potential for helping reduce mental health treatment disparities among minorities and other underserved populations" (78). Church-based, collaborative research processes could help build trust and reduce stigma associated with research that is especially strong in the African American community (8,(79)(80)(81).…”
Section: Discussionmentioning
confidence: 99%